Introduction: Towards a New Détente: Ecumenical Outreach and Interfaith Dialogue in an Age of Uncertainty - McDonald, William P. (Journal of ecumenical studies, 2020)
This is a report of the annual meeting of the North American Academy of Ecumenists, held September 27-29, 2019, at The Sign of the Theotokas Orthodox Church in Montreal. The theme involves the interface of ecumenical outreach and interfaith dialogue, within the contemporary social and intellectual context. The meeting featured four Canadian and two U.S. speakers from academia and/or grassroots practitioners who have had experience in both ecumenical and interfaith work.